Effect Submerged Arc Welding (SAW) of Angular Distortion of T-joint - Yusuf Pradesar; Pranowo Sidi (Athena: Journal of Social, Culture and Society, 2024)
Submerged Arc Welding(SAW),the molten weld metal is immersed in aflux that protects it from air contamination, forming welding slag which is strong enough to protect the weld metal until it solidifies. The used electrode was AWSA5.17EL12. The base metal being welded is ASTM A283 Grade A. In this study, the effect of angle distortion on the T joint was observed by changing the welding parameters. In order to obtain the optimal results, an attempt was made to link the welding parameters to the angle distortion through a mathematical model by using the Box Behnken statistic technique, the feasibility of which was then tested by using ANOVA analysis. What was obtained was analyzed with the help of the response surface methodology (RSM = Response Surface Methodology) then